Malaysia at the crossroads? The never-ending discourse between Islam, law, and politics - Steiner, Kerstin (Journal of religious and political practice, 2018)
Malaysia is a multiracial and multireligious society, with an intricate relationship between its different ethnicities, religions, and the state, which is often politically, socially, and legally loaded. The paper analyses the relationship between religion, law, and politics in Malaysia, which has been contentious since independence.There is no political consensus as to how this relationship should conceptualised.In recent years there has been an increasing trend towards the Islamisation of law and politics in Malaysia. This trend had far-reaching consequences illustrated in the discourses surrounding unilateral conversion of children and, of course, the implementation of hudud (Islamic criminal law) to name a few.Yet the pertinent question is whether this trend will change with the new political coalition in power since May 2018. Given the current political, social, and religious climate in Malaysia, this paper argues that a consensus on the definite role that Islam plays in Malaysia is unlikely to be reached. The positions between the defenders of secularism and the advocates for an increased role of Islam in the state have become more entrenched.